Differentiated tactics of surgical treatment of intervertebral disc herniation complicated by spinal canal stenosis - Ksenzov, Tymur A.; Khyzhnyak, Mykhaylo V. (Ukrainian Neurosurgical Journal, 2023)
Objective: to conduct a retrospective analysis and evaluate the results of various methods of surgical treatment of patients with intervertebral disc herniation (IDH), which is complicated by spinal canal stenosis (SCS) of the lumbar spine. Materials and methods: 80 patients (36 (45%) men and 44 (55%) women) with a diagnosis of IDH complicated by SCS took part in the study. The average age of patients is under 50 years. All patients were operated on in the neurosurgery department of Zaporizhzhya Regional Clinical Hospital between 2016 and 2020. Patients were divided into two groups depending on the area of ​​the spinal canal and the method of surgical treatment. Group A (n=20) – relative SCS, area of the spinal canal – 75‒100 mm2, the presence of IDH >6 mm (according to magnetic resonance imaging). These patients underwent a standard microdiscectomy. Group B (n=60) ‒ absolute SCS, spinal canal area <75 mm2, the presence of IDH <6 mm (according to magnetic resonance imaging). This category of patients underwent surgery with wide decompression of the spinal canal and stabilization of the spinal motion segment using the method of interbody and transpedicular fixation of the corresponding spinal motion segment. The postoperative follow-up period is up to 6 months. A visual analogue scale was used to assess the pain syndrome in the lower limb and back and the degree of its reduction in the postoperative period. The impact of surgical treatment on the quality of life of patients with IDH complicated by SCS was assessed using the Oswestry Disability Index questionnaire (ODI). Results. Before the operation in group B, an inversely proportional dependence of the pain syndrome level on the visual analogue scale on the age of the patients (p<0.05) and the duration of the disease (p<0.05) was recorded. No such dependence was found in group A. In both groups, a significant decrease in pain syndrome was noted at the end of the first day after surgery, with a further gradual decrease until the end of the observation period. When comparing groups at the end of the first day after surgery, after 3 and 6 months, no statistically significant differences were found (p>0.05). In both groups, a significant decrease in the Oswestry index was registered immediately after surgery and its further decrease until the end of the follow-up period. When comparing the groups at the end of the first day after the operation, after 3 and 6 months, no statistically significant differences were found (p>0.05), but preoperative Oswestry index was significantly higher in group B, (р=0.04 according to the Mann‒Whitney test). Conclusions. In group A, the treatment effectiveness of patients reached 80‒85%, in the observation period on the 3 and 6 months. In group B, the treatment effectiveness of patients was also high and amounted to 75‒80%, in the observation period on the 3 and 6 months. Thus, taking into account the high variability of clinical and morphological changes in patients with IDH complicated by SCS, it is optimal to use differentiated surgical treatment tactics.